Metallo-covalent organic frameworks for sonodynamic therapy - Yu, Bryan Geng Ding (Nanyang Technological University, 2025)
Sonodynamic therapy (SDT) is an emerging cancer treatment modality that uses ultrasound-activated sonosensitizers to induce cytotoxicity in cancer cells. SDT offers advantages over existing treatments, including deeper tissue penetration and high selectivity for tumour cells. Current SDT research primarily focuses on repurposing sensitizers from photodynamic therapy (PDT), limiting the discovery of novel sonosensitizers. 2D metallo-covalent organic frameworks (metallo-COFs) are a class of materials that are known to have high stability, tunability, periodicity and biocompatibility which makes them potential candidates as sonosensitizers for SDT. This project investigates the feasibility of metallo-COFs as potential sonosensitizers as well as the effects of changing metal species in the framework. Preliminary in vitro experiments demonstrated that these materials can effectively generate reactive oxygen species (ROS) and induce apoptosis in cancer cells upon ultrasound activation. These findings suggest that metallo-COFs may serve as promising candidates for SDT. Tuning of metal species coordination has also yielded additional properties such as chemodynamic therapeutic (CDT) properties for the potential of combinatorial treatments. Further optimization of their structure, biocompatibility, and ultrasound responsiveness is needed to facilitate their clinical translation for treating deep-seated tumours.